2006
DOI: 10.1158/0008-5472.can-06-1098
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Orally Active Small Molecule Potently Induces G1 Arrest in Primary Myeloma Cells and Prevents Tumor Growth by Specific Inhibition of Cyclin-Dependent Kinase 4/6

Abstract: Cell cycle deregulation is central to the initiation and fatality of multiple myeloma, the second most common hematopoietic cancer, although impaired apoptosis plays a critical role in the accumulation of myeloma cells in the bone marrow. The mechanism for intermittent, unrestrained proliferation of myeloma cells is unknown, but mutually exclusive activation of cyclin-dependent kinase 4 (Cdk4)-cyclin D1 or Cdk6-cyclin D2 precedes proliferation of bone marrow myeloma cells in vivo. Here, we show that by specifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(146 citation statements)
references
References 43 publications
5
141
0
Order By: Relevance
“…However, exogenous TGF-␤ failed to augment the loss of viability in freshly isolated CD138 ϩ primary BM myeloma cells (n ϭ 4) during 24 h of ex vivo culturing, or to induce cell cycle arrest based on the analysis of BrdU uptake, when proliferation was extended transiently ex vivo in coculture with HS-5 BMSCs and cytokines (33) (Fig. 1B).…”
Section: Tgf-␤ Is Secreted By Bmscs But It Fails To Induce Growth Armentioning
confidence: 99%
“…However, exogenous TGF-␤ failed to augment the loss of viability in freshly isolated CD138 ϩ primary BM myeloma cells (n ϭ 4) during 24 h of ex vivo culturing, or to induce cell cycle arrest based on the analysis of BrdU uptake, when proliferation was extended transiently ex vivo in coculture with HS-5 BMSCs and cytokines (33) (Fig. 1B).…”
Section: Tgf-␤ Is Secreted By Bmscs But It Fails To Induce Growth Armentioning
confidence: 99%
“…More recently, specific inhibition of Cdk4/6 by PD 0332991, an orally bioavailable small-molecule Cdk inhibitor Preclinical activity of P276-00 in myeloma N Raje et al has demonstrated growth arrest in MM cells. 37 PD 0332991 in combination with steroids triggered MM cell apoptosis suggesting its utility with conventional and novel agents. Here we show that P276-00 induces apoptosis in the majority of MM cells.…”
Section: P276-00 Is Active In An MM Xenograft Modelmentioning
confidence: 99%
“…5), (R)-roscovitine (CYC202/Seliciclib; refs. 11, 12), R547 (13,14), SNS-032 (15), PD-0332991 (16,17), AZD5438 (18,19), ZK 304709 (20,21), AG-024322, AT7519, and P276-00 (21).…”
Section: Introductionmentioning
confidence: 99%